ISLAMIC FINANCING TOOLS IN COMMERCIAL BANKS AND THEIR CONTRIBUTION TO ECONOMIC RESILIENCE - Safarova Nasiba Gulmurod qizi (Ecomind Press, 2025)
This article investigates the potential of Islamic financing tools implemented by commercial banks to enhance economic resilience, particularly in the context of financial instability, crises, and post-pandemic recovery. Islamic finance, rooted in the ethical and legal framework of Shariah law, offers a distinct set of financial instruments that emphasize asset-backing, risk-sharing, and socio-economic justice. The study analyzes the operational characteristics of Islamic financial products such as Mudarabah, Musharakah, Murabaha, Ijarah, and Sukuk and evaluates their macroeconomic implications on stability, financial inclusion, and long-term resilience. By employing a qualitative methodological approach and drawing on recent literature and institutional data from post-2020 publications, the article provides a comprehensive overview of how Islamic finance contributes to creating shock-absorbent financial structures within commercial banking systems.
Keywords: Islamic finance, economic resilience, commercial banks, Shariah-compliant instruments, Murabaha, Mudarabah, financial inclusion, crisis mitigation.